2015
DOI: 10.5812/ircmj.17(5)2015.17594
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns of Young Females and Their Association With Waist Circumference as a Health Index in Northwest of Iran, 2007

Abstract: Background:Despite the higher prevalence of overweight and obesity among young people in western countries, the 50th and 95th percentile ranks for waist circumference in the Iranian young Females are higher than those of the western ones.Objectives:Identifying major dietary patterns in Iranian young females, which associate with central obesity, can probably explain the difference between Iranian young females’ pattern and those of their western peers regarding obesity.Patients and Methods:In the current cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…These results agree with others who have not found significant differences in BMI and WC between children who followed a "western" dietary pattern or not [55][56][57]. However, other studies have shown significant differences in BMI and WC between an "unhealthy" or a "healthy" dietary pattern [52,58]. These discrepancies could be due to the heterogeneous origin and methodology of the studies, since there was only one European study, more specifically a Spanish study, and since each study used different dietary survey.…”
Section: Discussionsupporting
confidence: 91%
“…These results agree with others who have not found significant differences in BMI and WC between children who followed a "western" dietary pattern or not [55][56][57]. However, other studies have shown significant differences in BMI and WC between an "unhealthy" or a "healthy" dietary pattern [52,58]. These discrepancies could be due to the heterogeneous origin and methodology of the studies, since there was only one European study, more specifically a Spanish study, and since each study used different dietary survey.…”
Section: Discussionsupporting
confidence: 91%
“…Among the total studies, four studies observed no significant differences in BMI, WC and overweight prevalence and obesity prevalence among tertiles of those with a westernised dietary pattern compared with healthier dietary patterns and clusters (23,35,37,39) . Evidence of the relation between diet and anthropometric measures was observed in a study conducted in Iran by Alizadeh et al (29) . Subjects of the top tertile of the 'Iranian Central Obesity Making Dietary Pattern' (composed by cruciferous vegetables, green leafy vegetables, soft drinks, tomatoes, other vegetables and vegetable oils) group had higher WC than subjects in the lowest tertile (P = 0•03).…”
Section: Dietary Pattern and Bmi And Waist Circumferencementioning
confidence: 87%
“…Alizadeh et al (29) + Zamora-Gasga et al (28) Partially Cannot determine or measurement approach not reported was significantly associated with DBP (P = 0•025), with participants with higher scores having lower BP (adjusted for age, sex and physical activity). There were no significant associations between any of the dietary patterns and SBP after adjustment for confounders.…”
Section: Dietary Patterns and Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Total energy intake (kcal/day) of subjects was calculated according to the data available at USDA (United States Department of Agriculture) national nutrient database [ 20 ] or other sources [ 21 , 22 ]. Then, food items were categorized into 30 separate groups based on the previous studies [ 23 , 24 ] or similarities in their nutrient profile. The FFQ was validated with two 24/h dietary recalls and the correlation coefficients ranged from 0.08 (low fat dairy products) and 0.64 (for high fat dairy products) for food groups.…”
Section: Methodsmentioning
confidence: 99%